Pasipiri Bukkang: Socio-Economic Dynamics of Coastal Communities and Implications for Increasing Mangrove Crab Production in Bone Regency - Triadi, Feby; Asdar, Muhammad; Faidzaturrahmah, Nur; Arif, Arnawan; Awaluddin A, M (Pinisi Business Administration Review, 2025)
Mangrove ecosystems play a strategic role in maintaining the balance of the coastal environment while simultaneously supporting the local economy, particularly through commodities such as mangrove crabs. However, the relationship between conservation and productivity is often fraught with tension, particularly when economic pressures and external interventions are not aligned with local value systems. This study aims to examine the socio-economic construction of coastal communities in Bone Regency. A qualitative approach was used, using a case study method, collecting data through in-depth interviews, participant observation, and documentation. Data were then analyzed thematically, supported by the theoretical frameworks of Berger & Luckmann, Bourdieu, and Giddens. The research findings indicate that communities collectively understand mangroves as both ecological and economic entities, shaped by empirical experience and local values. This construction directly impacts attitudes toward conservation: communities that view mangroves as part of life are more likely to preserve them. However, short-term economic pressures, unequal access to information, and decontextualized intervention programs create a paradox between the needs of productivity and sustainability. The study concludes that successful conservation depends not only on an ecological approach alone, but also on a deep understanding of the social logic of coastal communities.